Vascular Gap Junctions Contribute to Forepaw Stimulation-Induced Vasodilation Differentially in the Pial and Penetrating Arteries in Isoflurane-Anesthetized Rats - Watanabe, Nobuhiro; Sasaki, Satoshi; Masamoto, Kazuto; Hotta, Harumi (Frontiers in Molecular Neuroscience, 2018)
Somatosensory stimulation causes dilation of the pial and penetrating arteries and an increase in cerebral blood flow (CBF) in the representative region of the somatosensory cortex. As an underlying mechanism for such stimulation-induced increases in CBF, cerebral artery dilation has been thought to propagate in the vascular endothelium from the parenchyma to the brain surface. Vascular gap junctions may propagate vasodilation. However, the contribution of vascular gap junctions to cerebrovascular regulation induced by somatosensory stimulation is largely unknown. The aim of the present study was to investigate the contribution of vascular gap junctions to the regulation of the pial and penetrating arteries during neuronal activity attributed to somatosensory stimulation. Experiments were performed on male Wistar rats (age: 7–10 weeks) with artificial ventilation under isoflurane anesthesia. For somatosensory stimulation, the left forepaw was electrically stimulated (1.5 mA, 0.5 ms, and 10 Hz, for 5 seconds). The artery in the forelimb area of the right somatosensory cortex was imaged through a cranial window using a two-photon microscope and the diameter was measured. Carbenoxolone (CBX) was intravenously administered, at a dose of 100 mg/kg, to block vascular gap junctions. The forepaw electrical stimulation increased the diameter of the pial and penetrating arteries by 7.0% and 5.0% of the pre-stimulus diameter, respectively, without changing the arterial pressure. After CBX administration, the change in pial artery diameter during forepaw stimulation was attenuated to 3.2%. However, changes in the penetrating artery were not significantly affected. CBF was measured using a laser speckle flowmeter, together with somatosensory-evoked potential recorded in the somatosensory cortex. The extent of CBF increase (by 24.1% of the pre-stimulus level) and amplitude of somatosensory evoked potential were not affected by CBX administration. The present results suggest that vascular gap junctions, possibly on the endothelium, contribute to pial artery dilation during neuronal activity induced by somatosensory stimulation.